GEMPA BUMI MERUSAK JAWA TIMUR SELATAN 10 APRIL 2021 - Nia Kurnia Praja; Supartoyo; Amalfi Omang (PPSDM Geominerba, 2021)
On April 10th, 2021, at 14:00 local time, there was a destructive earthquake in the southern part of East Java area from the intraslab zone, resulting 9 people victim in Malang and Lumajang regency, 121 people injuries in Malang and Blitar regency, and thousands of buildings damage in the area of ​​South East Java. Also, this earthquake has triggered a small landslide and soil cracks type of lateral spreading. The maximum earthquake shaking occur in the southern part of Malang and Lumajang regency with earthquake intensity scale of MMI (Modified Mercally Intensity). Result of surface shaking modelling in the southern of East Java region ranged from 0.092 g (gravity) to 0.13 g.